Paracetamol use (and/or misuse) in children in Enugu, South-East, Nigeria - Obu Herbert A; Chinawa Josephat M; Ubesie Agozie C; Eke Christopher B; Ndu Ikenna K (BMC, 2012)
Abstract Background Paracetamol (also known as acetaminophen) is the commonest available analgesic and anti-pyretic. It is readily accessed from pharmacy, patent medicine and provision shops as over the counter drug making it a potential drug of abuse, especially in children. We sought to find its use and/or misuse in children seen at the paediatric outpatient clinic of the University of Nigeria Teaching Hospital (UNTH) Ituku-Ozalla, Enugu. Objective To determine the dosage, formulation, and frequency of paracetamol administration to children by caregivers and factors associated with its use and/or misuse. Method An observational prospective study involving 231 children and their caregivers seen at the paediatric outpatient clinic of the University of Nigeria Teaching Hospital, Ituku - Ozalla, Enugu between June and November 2011 was undertaken. Data on paracetamol use before presentation to the clinic, in addition to demographic and other data were obtained from the caregivers using a structured questionnaire. Ethical consent for the study was obtained from the Hospital Ethics and Research Committee and informed consent was further obtained from the caregivers of the children. Results A total of 231 children aged six weeks to 16 years and their caregivers participated in this study. The mean ages of the children and their caregivers were 3.8 and 33.9 years, respectively. One hundred and thirty three of the children studied were males while 98 were females. Most of the children (75.6%) received paracetamol at home before presenting. Paracetamol tablet alone or in combination with the syrup was mostly used (60%) and this observation was made across all age groups. The commonest reason for using paracetamol tablet instead of the syrup was that it was more effective. Most caregivers relied on past experience (71.2%) rather than on enclosed information leaflet to decide the appropriate dosage. Half of the children also received other medications, mainly anti-malarials and antibiotics. Conclusions Paracetamol was commonly given to children on "self prescription" basis and the tablet formulation was most frequently used, with the possibility of misuse and overdose. Caregivers need to be educated on age-appropriate formulations which are less likely to lead to overdose.